Processing and properties of porous Ti-Nb-Ta-Zr alloy for biomedical applications using the powder metallurgy route - Nugroho, Aris; Leadbeater, Garry; Davies, Ian (Engineers Media Pty Ltd., 2011)
Titanium alloys, due to their biocompatibility and low stiffness, are among the most studied of metallic implant materials. Whereas most titanium-based biomaterials are produced from prealloyed powders, in this work the authors have utilised elemental powder to manufacture porous Ti-Nb-Ta-Zr alloys using a powder metallurgy technique based on the pressurized gas-induced expansion of pores. Samples of porous Ti-Nb-Ta-Zr alloy were prepared from a blend of elemental powders sealed into steel cans under a pressurised argon atmosphere. Following this, the pressurized cans were densified by hot isostatic pressing (HIP) at 1100oC and 100 MPa for 4 hours, with cubic specimens from each can being treated in a vacuum furnace (1100oC, 1225oC, 1350oC) for 10 hours in order to allow the pressurized pores to expand due to creep of the surrounding metal (foaming). Following this, the phase composition of HIP-ed and foamed samples was characterized by X-ray diffraction (XRD), whilst microstructure and pore morphology were examined using optical microscopy and scanning electron microscopy. Mechanical testing under compressive loading was carried out at a strain rate of 10-3 s-1. Following HIP-ing, XRD indicated the suppression of peaks related to -Ti whilst microstructural analysis revealed the particle boundaries to have become diffuse due to the partial dissolution of Nb and Ta, with initial porosity levels being generally less than 3 %. Increasing the foaming temperature led to increases in porosity and proportion of -Ti phase with a resulting decrease in elastic stiffness. These porous materials were concluded to be an attractive candidate for low stiffness biocompatible implant materials.